Perspectives on Recruitment and Representativeness in Forensic Psychiatric Research - Pedersen, Sven H.; Bergman, Henrik; Berlin, Johan; Hartvigsson, Thomas (Frontiers in Psychiatry, 2021)
Participant representativeness and statistical power are crucial elements of robust research with human participants, both of which relate to the successful recruitment of research participants. Nevertheless, such core features may often not be fully reported or duly considered in psychiatric research. Building on our experiences of collecting data in the context of forensic mental health services, we discuss issues regarding participant recruitment and representativeness in our field with its particular characteristics. A quick sampling and brief overview of the literature in four specialized forensic mental health journals is presented, demonstrating that published manuscripts rarely describe the data in sufficient detail for the reader to assess sample representativeness and statistical power. This lack of transparency leads not only to difficulties in interpreting the research; it also entails risks relating to the already meagre evidence base of forensic mental health services being relevant only to a subset of patients. Accordingly, we provide suggestions for increased transparency in reporting and improved recruitment of research participants. We also discuss the balance of ethical considerations pertinent to the pursuit of increased participation rates in forensic mental health research.